Interactions at the interface of polymer matrix-filler particle composites. (26th October 2016) - Feng, Jie; Venna, Surendar R.; Hopkinson, David P.
Abstract: Interfacial structures of polymer matrix-filler particle composites play a crucial role in determining the properties of the composite materials, such as the gas separation performance of mixed matrix membranes. Monte Carlo simulations employing coarse-graining models show that the density distribution and the fraction of free volume of the polymer at the interface are dominated by the interaction of the polymer with the filler particle and the geometry of the filler particle surface. Here, we studied two different filler particles with smooth and brush-like (rough) surfaces and three different polymer chains with rigid, medium and soft flexibility. Five different interaction strengths between the polymers and filler particles were studied. The polymer chains deform into pancake-like conformations on the filler particle surface in all the cases. Interestingly, the polymer chains are deformed more on the surfaces of particles that have strong repulsion in comparison to attractive and neutral surfaces. Filler particles that have brush-like surfaces tend to results in larger free volume at the interface than occurs with smooth surfaced filler particles. By contrast, the rigidity of the polymer chain introduced by considering the angle potential in the coarse-grain model only slightly influences the chain conformation at the interface. Graphical abstract: Highlights: The surface morphology and interaction between polymer/filler are crucial factors dominating the interfacial properties. Polymer chains experienced the most notable flattening or "pancake" deformation were in contact with a repulsive surface. Brush-like pendant structures attached to particles create bigger void space at the interface.